SOCIAL AND ECONOMIC ASPECTS IN THE CREATIVE WORK OF VASYL STEFANYK - Savkiv, Uliana; Sydor, Halyna (Mountain School of Ukrainian Carpaty, 2021)
The analysis of Vasyl Stefanyk's novelistic creative work from the standpoint of social and economic aspect has been presented. The influence of social and economic factors on the psychological state of peasants in the second half of the 19th – early 20th century has been revealed, the comparative analysis of social and economic situation of Ukrainians at the present stage and during creative work of the writer has been conducted. Today, as in Vasyl Stefanyk's short stories, we are experiencing the social and economic consequences of the war, forced emigration, rapid impoverishment of the population and we do not always conduct successful attempts for overcoming social injustice. In Ukraine, there are no clear concepts and strategies for overcoming the negative trends in the national economy that exist in European countries. The solution of social and economic problems lies in the plane of reforms not only in the economy, but also in education, culture and national consciousness. Studying the works of Vasyl Stefanyk is an efficient way to comprehend the historical past and change the present. The introduction of decentralization of governance and rendering possibilities for regions to solve social and economic development problems on their own is an important step towards solving social and economic problems of the regions. At the same time, an important factor that will ensure successful decentralization at the state level is the provision of not only corresponding powers to the regions, but also financial resources. The solution of social and economic problems lies in the plane of reforms not only in the economy, but also in education, culture and national consciousness. Studying the works of Vasyl Stefanyk is an efficient way to comprehend the historical past and change the present.